Blame It on the Sun: George Jackson and Poetry of Palestinian Resistance. (2nd October 2015) - Thomas, Greg
Abstract : This essay explores the political significance of a literary 'mistake' made in 1971 in the historical context of Black/Palestinian solidarity. After the assassination of George Jackson, the revolutionary prisoner who had been recently designated Field Marshal of the Black Panther Party, prison guards seized Palestinian resistance poetry from his prison cell in San Quentin, California. Some of this poetry by Samih Al-Qasim, Palestinian resistance poet par excellence, was thought to be written by Jackson and published under his name in the Black Panther newspaper. An uncanny resemblance between the voices of Jackson and Al-Qasim, as well as the conditions of Blacks in North America and Palestinians, made this 'mis-attribution' possible. It is thus argued that what might be viewed as a literary 'mistake' instead can be viewed as a powerful illustration of kinship in the practice of revolutionary political solidarity. Ultimately, this solidarity would be recalled and renewed in a 2015–16 exhibition featuring George Jackson at the Abu Jihad Center for Prisoner Movement Affairs in Palestine.